Peningkatan Hasil Belajar Melalui Penerapan Strategi Pembelajaran The Power Of Two and Four Mata Pelajaran Fikih Materi Puasa di MTs Darul Ulum Ngaliyan Semarang - Siti Masri'ah (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2016)
This study aims to determine the learning outcome Fiqh using strategies the power of two and four. This research is a classroom action research conducted on students of class VIII-B MTs Darul Ulum. The results showed that after the implemented action with the strategy of the power of two and four, the atmosphere became more active learning and classroom come alive, learners become the spirit of learning and learning outcomes maximum. The research was conducted in three phases: pre-cycle, the first cycle, and the cycle 2. At the stage of pre-cycle spirit of learners have a percentage of 48.27% and average values ​​to the end of the 66.20% in cycle 1 after the implemented action spirit learners increased to 68.96% and the average value of the test 76.37%, while in cycle 2 after evaluation implementation cycle action 2 spirit learners has risen 93.10% and the average of the final test of learners is 86, 89%. Of the three stages is clear that there is increased before being applied learning models the power of two and four before.